DETERMINAN STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR DI BEI - Tri Nurjanah; Nur Wahyuning Sulistyowati (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2020)
ABSTRACTThis study aims to prove that the capital structure and size of the company affect the company's financial performance. The method used in this study is descriptive quantitative with purposive sampling technique. Data analysis techniques using multiple linear regression. This research was conducted at IDX. The results of this study indicate a significant determinant of capital structure on the financial performance of the company, and the size of the company does not affect the company's financial performance. Due to the high or low size of the company does not affect the company's financial performance and does not guarantee good performance. While simultaneously has a significant positive effect on the company's financial performance.